Apakah Kapitalisme (Global) Memiliki Moral? - Stanislaus Nugroho (Respons: Jurnal Etika Sosial, 2008)
The question of morality is an old problem in economics enterprise. Karl Marx had exposed that questioning as the main problem in his inquiring of the logic of capitalism. His criticism of capitalism suggested that capitalism had to look for a more human attitude: to be a human capitalism. But that kind if human capitalism cannot be found. Capitalism has created problem of economic justice. While capitalism makes some part of the world more human, another part of the world suffers with hunger and poverty.